Optical Impression Systems for CAD-CAM Restorations - Prado Galhano, Graziela Avila [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Mazaro, José Vitor Quinelli [UNESP] (Lippincott Williams & Wilkins, 2012)
Computer-aided design/computer-aided manufacturing images can be taken through either direct or indirect imaging. For the indirect systems, the digitalization is obtained from the impression material or cast, and for the direct ones the image is taken directly from the mouth using intraoral scanners.The direct acquisition systems have been constantly improved because these are less invasive, quicker, and more precise than the conventional method. Besides, the digital images can be easily stored for a long time. Therefore, the aim of this paper was to describe and discuss based on the literature the main direct image acquisition systems available on the market: CEREC Bluecam (Sirona), Lava C.O.S. System (3M ESPE), iTero System (Cadent/Straumann), and E4D System (D4D Technologies).
Keywords: CAD-CAM; digital impressions